Photodynamic therapeutic activity of novel porphyrins against lung squamous cell carcinoma - Hao Meng; Ren-Quan Ding; Lei Jia; Xiang-peng Chen; Yu-hang Hu; Shu-min Wang; Si-qi Lv; Fan Feng (BMC Cancer)
Abstract Porphyrins, as drug-food homologous bioactive substances, hold significant potential in nanomedicine research and photodynamic therapy (PDT). In this study, we synthesized two novel porphyrin compounds, PTA and PTBA, based on the porphyrin compound TCPP. Using these compounds, we prepared metal-porphyrin nanoparticles and evaluated their properties. Results from multiple assays demonstrated that both PTA and PTBA exhibited significantly enhanced photodynamic therapeutic activation under laser irradiation compared to TCPP. This included improved reactive oxygen species (ROS) and singlet oxygen release, as well as superior antitumor activity. When prepared as metal-porphyrin nanoparticles, all three compounds—PCN224 (TCPP with Zr⁴⁺), PMOF01 (PTA with Zr⁴⁺), and PMOF02 (PTBA with Zr⁴⁺)—showed significantly upregulated photodynamic therapeutic effects. These nanoparticles induced the accumulation of ROS and singlet oxygen in lung squamous cell carcinoma (LSCC) cells and demonstrated both in vitro and in vivo antitumor activity under laser irradiation. Notably, PMOF01 and PMOF02 exhibited much stronger antitumor effects compared to PCN224 in LSCC cells. Our findings highlight the photodynamic therapeutic potential of these novel porphyrin compounds and their nanoparticles. These results not only expand our understanding of porphyrins’ antitumor capabilities but also provide new options for PDT applications.